POLITICAL AND ECONOMIC RELATIONS of TURKEY AND PEOPLE'S REPUBLIC OF CHINA (International relations and international law Journal, 2016)
In this article the political and economic issues of TurkishChinese relations are considered.
Keywords: foreign policy; Turkey; China